Aesthetics and politics in the Capitalocene: considerations in search of an aesthetic pluralism - Souza, Mateus Raynner André de (Farol, 2023)
Abstract: Starting from the emergence of the creation of names and concepts to understand the new geological epoch, and following recent research in art history, this essay will analyze the Capitalocene, that is, the intrusion of capitalism as a geological force and as an aesthetic phenomenon. We consider that in addition to the climate crisis, a cultural and aesthetic crisis was established, all of which are closely linked. To understand this new status of the Earth, it is necessary to analyze how cultural capitalism depoliticizes the aesthetic field and how art and aesthetics corroborated with the establishment of the current crises, we used colonial missions as a parameter of analysis as a demonstration of the problem. In this way, as a counterproposal, we envision aesthetic solutions to the Capitalocene, these based on community, political and pluralistic bases. Keywords: Art and Anthropocene. Aesthetics and Politics. Capitalocene. Aesthetic Community. Aesthetic Pluralism.